Aspects of economic life in the central Moroccan desert through the hidden pearls of Al-Mazouni - kichah, Hisham; gueriene, adjalil (The Algerian Historical Journal, 2026)
This study examines the features of economic life in the countryside of the Central Maghreb during the Ziyanid period, based on legal and historical data from al-Durrar al-MaknūnafīNawāzilMāzūna by Imam al-Māzūnī (d. 883 AH/1478 CE). The nawāzil highlight the role of rural activity in supplying urban centers with agricultural products, livestock, and raw materials, as well as in commercial exchange with cities. The study concludes that rural and urban domains formed an integrated economic and social space, and that the nawāzil represent an important source for understanding this interaction in its economic, social, and cultural dimensions.